Insights: The conceptual framework for building the world class good governance ethics - Wan Ahmad Fauzi, Wan Husain (Universiti Malaysia Pahang, 2020)
Good governance without ethics is a corpse. Both must coexist to define morality of behavior be it in individual self or group of people or an organization. The Renaissance gave birth to schools of thought that adopted secularism to define humanity and rights even though the teaching of religions are still an essence for personal aspects of life. Hence, this paper introduces the conceptual framework for building the World class good governance ethics as articulated from the conduct of Prophet Muhammad SAW, who has been recognized as the most influential people in history by Michael H Hart. This conceptual framework will help individual as well as private and public enterprises to seek the essence of moral principles as guidance for good governance ethics. In conclusion, the World class good governance ethics is the conduct of management and behavior within an organization or individual that comply with the principles of faith, accountability, disruptive leadership, integrity, trustworthiness underpinned with the practice of consultation towards the achievement of justice